2005
DOI: 10.1021/es050350r
|View full text |Cite
|
Sign up to set email alerts
|

Natural Humics Impact Uranium Bioreduction and Oxidation

Abstract: Although humic substances occur ubiquitously in soil and groundwater, their effect on the biological reduction of uranium(VI) and subsequent reoxidation of U(IV) is poorly understood. This study investigated the role of humics in enhancing the bioreduction of U(VI) in laboratory kinetic studies, in field push-pull tests, and in the presence or absence of metal ions such as Ca2+ and Ni2+, which are known to inhibit the biological reduction of U(VI). Results from laboratory experiments indicate that, under stric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
141
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(147 citation statements)
references
References 45 publications
3
141
1
Order By: Relevance
“…It is well-known that the Pseudomonas genus comprises many hydrocarbon-degrading bacteria both in aerobic and anaerobic conditions (Haritash and Kaushik 2009). On the other hand, microbial-mediated humus reduction may highly be related to the anaerobic biodegradation of organic or inorganic pollutants (Gu et al 2005;Wang et al 2009). Previous literatures have reported that AQDS (and humic substances) can be utilized by microbes as effective electron acceptors or shuttles for the oxidative degradation of organic pollutants, such as 1,2-dichloroethylene, vinyl chloride, toluene, and phenolic compounds (Bradley et al 1998;Cervantes and Dijksma 2001;Cervantes et al 2000).…”
Section: Effect Of Electron Donors On Aqds Reduction By Strain Pah-1mentioning
confidence: 99%
“…It is well-known that the Pseudomonas genus comprises many hydrocarbon-degrading bacteria both in aerobic and anaerobic conditions (Haritash and Kaushik 2009). On the other hand, microbial-mediated humus reduction may highly be related to the anaerobic biodegradation of organic or inorganic pollutants (Gu et al 2005;Wang et al 2009). Previous literatures have reported that AQDS (and humic substances) can be utilized by microbes as effective electron acceptors or shuttles for the oxidative degradation of organic pollutants, such as 1,2-dichloroethylene, vinyl chloride, toluene, and phenolic compounds (Bradley et al 1998;Cervantes and Dijksma 2001;Cervantes et al 2000).…”
Section: Effect Of Electron Donors On Aqds Reduction By Strain Pah-1mentioning
confidence: 99%
“…NOM contain redoxactive functional groups, such as quinones, and have the ability to form NOM-metal complexes (Haack & Warren 2003). NOM, or humic substances, are known to be redox reactive with elements in soil Struyk and Sposito 2001) and therefore capable of reducing redox-sensitive metals such as Cr(VI) (Wittbrodt & Palmer 1995;Nakayasu et al 1999;Zhilin et al 2004;Banks et al 2005), Mn(IV) (Sunda & Kieber 1994), V(V) (Lu et al 1998), As(V) (Redman et al 2002), U(VI) Gu et al 2005) and Hg(II) (Alberts et al 1974;Matthiessen 1996). …”
Section: Transport and Redox Reactionsmentioning
confidence: 99%
“…Humic acid was found to be more effective than fulvic acid in enhancing the reduction of U(VI). Such an enhancement effect is attributed to the ability of these humics in facilitating electron-transfer reactions and/or in complexing Ca 2+ and Ni 2+ ions (Gu et al 2005). Gu et al (2005) showed that humics were also found to form complexes with reduced U(IV) and increased the oxidation of U(IV) when exposed to oxygen.…”
Section: Transport and Redox Reactionsmentioning
confidence: 99%
“…However, the detailed study of uranium-humic or -fulvic acid complexes has not yielded structures due to the complexity of the organic compound despite the use of powerful techniques such as X-ray absorption spectroscopy (Schmeide et al, 2003). In addition, microbially-catalyzed reduction of metals in organic matter-rich environments was observed in which microorganisms use metals as terminal electron acceptors and the humic substances as donor or as an electron shuttle for anaerobic respiration (Lovley et al, 1996;Gu and Chen, 2003;Gu et al, 2005;Grybos et al, 2007;Wall and Krumholz, 2006). As a result of the inherent complexity of these systems, the underlying chemical processes responsible for U accumulation in organic-rich soils are still poorly understood.…”
Section: Introductionmentioning
confidence: 99%